2006
DOI: 10.1172/jci26582
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory role for the C5a anaphylatoxin in type 2 immunity in asthma

Abstract: Complement component 5 (C5) has been described as either promoting or protecting against airway hyperresponsiveness (AHR) in experimental allergic asthma, suggesting pleomorphic effects of C5. Here we report that local pharmacological targeting of the C5a receptor (C5aR) prior to initial allergen sensitization in murine models of inhalation tolerance or allergic asthma resulted in either induction or marked enhancement of Th2-polarized immune responses, airway inflammation, and AHR. Importantly, C5aR-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
232
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(247 citation statements)
references
References 62 publications
14
232
0
Order By: Relevance
“…Later, Kim et al (12) observed that mice treated with C5aR antagonist have impaired CD8 T cell response to influenza type A virus, suggesting that C5a-C5aR interaction plays an important role in generation of Ag specific T cell responses. In contrast to in the virus model, Kohl et al (34) found that in the asthma model, blocking C5aR resulted in induction of marked enhancement of Th2 immune response, suggesting that C5a-C5aR interaction down-regulates Th2 immune response which is thought to play a critical role in asthma pathogenesis. Recent studies reported that when APC and T cell were encountered, C5a interaction with C5aR on both cells can provide costimulatory and survival signals to naive CD4 T cells, thus up-regulate Ag-specific T cell responses (14).…”
Section: Discussionmentioning
confidence: 97%
“…Later, Kim et al (12) observed that mice treated with C5aR antagonist have impaired CD8 T cell response to influenza type A virus, suggesting that C5a-C5aR interaction plays an important role in generation of Ag specific T cell responses. In contrast to in the virus model, Kohl et al (34) found that in the asthma model, blocking C5aR resulted in induction of marked enhancement of Th2 immune response, suggesting that C5a-C5aR interaction down-regulates Th2 immune response which is thought to play a critical role in asthma pathogenesis. Recent studies reported that when APC and T cell were encountered, C5a interaction with C5aR on both cells can provide costimulatory and survival signals to naive CD4 T cells, thus up-regulate Ag-specific T cell responses (14).…”
Section: Discussionmentioning
confidence: 97%
“…In the lung, PDCs are among the earliest inflammatory cells to enter the bronchoalveolar space following influenza A virus infection [81], and support the recruitment of CXCR3 + and CCR5 + effector T cells through the local secretion of CXCL10 and CCL5 [82]. A protective role for C5a in allergic asthma has been linked to a shift in the MDC/PDCs ratio toward PDCs, with an accompanying decrease in CCL17 production [83]. Furthermore, PDCs depletion exacerbates respiratory syncytial virus lung immunopathology [84].…”
Section: Modulation Of Leukocyte Recruitment By Pdcsmentioning
confidence: 99%
“…Similar results are observed when C5aR is blocked prior to initial pulmonary HDM challenge. Together, this data suggests that the presence of C5a in the airways at the time of initial allergen encounter serves to prevent the development of Th2-mediated immune response (Kohl et al, 2006). Protection against allergic sensitization by C5aR activation is a complex process involving alterations in the function of APCs, in particular dendritic cells.…”
Section: Allergic Inflammation: Allergic Asthmamentioning
confidence: 83%
“…CD4 + T cells from mice challenged with HDM allergen in presence of an anti-C5aR monoclonal antibody produce higher levels of Th2 cytokines in co-culture with mDCs, but not with pDCs. Importantly, in the same setting, pDCs suppress the mDC-induced production of Th2 cytokines (Kohl et al, 2006). Furthermore, exposure to HDM leads to an increased number of mDCs, whereas the number of pDCs remains unaffected.…”
Section: Allergic Inflammation: Allergic Asthmamentioning
confidence: 95%